Managing organizational knowledge transfer in requirements elicitation process - Che Pa, Noraini; Hassan, Sa'adah; Jusoh, Yusmadi Yah (2014)
The organizational knowledge highlights the capability of members in the organization in carrying out their work, and using their collective understanding and experiences in the business process. The organizational knowledge transfer is important for sustaining and enhancing organizations’ competitive advantage. Knowledge transfer during the requirements elicitation process is crucial in order to attain a consensus between customers and developers in respect of all issue that required for a system. In order to achieve that, they need to effectively and efficiently organize and manage the process of knowledge transfer, within intra-organization as well as inter- organizations. The aim of this paper is to show the structural components that engage in knowledge transfer and how the organization can manage the transfer.